Adultos mayores dependientes hospitalizados: La transición del cuidado (2007)
ABSTRACT: According to the theory of transition during the hospital entry-stay-leave sequence there are favorable moments to guide the sick person and his family about care and its continuity back home. Objective: To describe the transition process from hospital care to the dependent aged person house. Methodology: Focused ethnography. Thirty semi structured interviews were performed with aged people, relatives and professionals from ﬁve public and private institutions. In Medellin, Bello and Rionegro (Antioquia, Colombia) 25 participating observations were performed in 9 hospital wards and data was manually analyzed according to ethnographic guidelines. Results: The “sick aged people and their families: Much more than the illness” theme was highlighted to describe how people feel they are subjects demanding integral care rather the “patients”; the cared subject objectivation of the interaction loss between sick person and caring person and how the transition between hospital and home took place. Conclusions: The aged person leaves hospital without knowledge about how to follow the treatment at home. Accordingly it is necessary that the caring personnel give adequate consideration to the hospital-home care transition process.